Diversifikasi tanaman herbal menjadi produk minuman untuk masyarakat lokal dan wisatawan - Dewa Komang Tantra,; I Wayan Rasna, (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
The purpose of this research was to analyze traditional herbs in the lontar usadha or traditional healing books and those which were frequently used by the traditional healers in Bali. These traditional herbs studied for potential diversification as local society’s drink or tourist’s wellcome drink. The sample were taken purposively and they consisted of 18 lontar usadha, 15 balian or traditional healers, and 20 tourism school teachers and lecturers. Data on traditional herbs in the lontar usadha were collected using a content analysis technique. Data on traditonal herbs used by balian or traditional healers were collected through an in-depth interview technique. Whereas, data on traditional herbs are potentially diversified as society’s drink and tourist’s wellcome drink were collected using a questionnaire. The questionaire was administered to teachers and lecturers of Culiniary Department, School of Tourism in Bali. Data were analyzed descriptively qualitative. The analysis of the lontar usadha’s contents, balian’s in-depth interview, teachers and lecturers’ questionnaire show 20 traditional herbs are potentially diversified as local society’s drink or tourist’s welcome drink.
Keywords: lontar usadha; balian; society’s local drink; tourist’ wellcome drink